AB0640 LONG-TERM EFFECTIVENESS AND DRUG SURVIVAL OF GOLIMUMAB IN PATIENTS AFFECTED BY PSORIATIC ARTHRITIS WITH CUTANEOUS INVOLVEMENT. (2nd June 2020) - Fonti, G. L.; Chimenti, M. S.; D'antonio, A.; Teoli, M.; Caso, F.; Costa, L.; Tasso, M.; Ortolan, A.; Lorenzin, M.; Conigliaro, P.; Triggianese, P.; Scarpa, R.; et al.
Abstract : Background: Psoriatic arthritis (PsA) is a chronic immune-mediated disease associated with psoriasis (PsO). Overexpression of inflammatory cytokines such as tumor necrosis factor (TNF)-α plays a key role in the pathogenic mechanisms. Golimumab (GLM) is a fully human monoclonal antibody IgG1k neutralizing TNF-α approved for PsA and PsO, but effectiveness evaluation in real life remains a crucial issue. Objectives: In a real-life setting, to determine the survival rate of GLM (drug survival) at 48 months in the global population, in different clinical settings, and the effectiveness of GLM in improving joint symptoms and cutaneous manifestations in patients affected by moderate to severe PsA with cutaneous involvement. Methods: We collected retrospectively from 1 January 2014 to 31 December 2019 data from 105 patients affected by PsA, according to the Classification for Psoriatic Arthritis (CASPAR) criteria, who started treatment with GLM. Inclusion criteria were age > 18 years and had a diagnosis of PsA > 6 months, the presence of peripheral arthritis (at least one active joint) and active PsO. Relevant anamnestic, clinical, biochemical data and biological treatment line were collected at baseline (T0) and after 6 (T6), 12 (T12), 24 (T24) and 48 (T48) months of GLM treatment. Comparisons between baseline and 48 months continuous variables were performed using a paired t-test or a Wilcoxon signed-rank test for paired samples. The drug survival rates were analyzed using Kaplan-Meier estimates. Drug survival rates were read from the Kaplan-Meier survival curves. Differences in drug survival between groups were analyzed using a log-rank (Mantel-Cox) test, by stratifying for sex, BMI, smoking habit and line of treatment. A p-value <0.05 was considered as statistically significant. Results: Peripheral arthritis was present in 67 (63.8%) cases, axial disease in 37 (35.3%), enthesitis and PsO as prominent manifestations in 82 (78%) and 84 (80%) patients respectively. Erosive disease was present in 38 (36.2%) of patients at baseline. The most frequent comorbidities were MetS described in 20 (19%) patients and cardiovascular disease described in 33 (31.4%) patients, probably due to the high incidence of smokers (33 (31.4%) of patients) and to the elevate BMI score (27.1±6.0). At 48 months, the 42% (44 of 105) (figure 1A ) of the patients have discontinued therapy; the most frequent reason was insufficient response/loss of efficacy (30 patients (28.6%) out of 105). Unexpectedly, no statistical significant difference emerged according to gender (p=0.652), BMI (p=0.655), smoking habit (p=0.466) and line of treatment (p=0.208) (figure 1B -E). Finally, the effectiveness of GLM in improving joint symptoms and cutaneous manifestations was confirmed once again, with a statistical significant improvement at 48 months in clinical (BASDAI p<0.0001; PASI p<0.01; DAPSA p<0.0001) and biochemical (CRP<0.05) data. Conclusion: This multicentric study revealed a high drug persistence of GLM in real-life patients, although the presence of comorbidities. Unlike what is known in literature, our study population presented no differences in terms of clinical response and efficacy between male and female, smokers and no-smokers, obese and health-weight patients, different line of treatment. On the other hand, efficacy and safety of GLM has been demonstrated once again also in real-life treatments. References: No references. Disclosure of Interests: giulia lavinia fonti: None declared, Maria Sole Chimenti: None declared, Arianna D'Antonio: None declared, miriam teoli: None declared, Francesco Caso: None declared, Luisa Costa: None declared, marco tasso: None declared, Augusta Ortolan: None declared, Mariagrazia Lorenzin: None declared, Paola Conigliaro: None declared, paola triggianese: None declared, Raffaele Scarpa: None declared, Roberto Perricone: None declared, Roberta Ramonda Speakers bureau: Novartis, Celgene, Janssen, Pfizer, Abbvie, Lilly